PENGELOLAAN TEMPAT PELELANGAN IKAN (TPI) DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT NELAYAN - Moh Ainur Rizqi (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2021)
The fish auction in Paiton District is a means of transactions for marine products, fish catches produced by fishermen that should be auctioned off and managed by TPI, but the management and utilization of TPI Paiton is considered not optimal due to several constraints and available facilities. The results showed that: 1) the management of the Fish Auction Place (TPI) in Paiton District has carried out its duties and functions properly, namely the facilities and functions have been utilized by fishermen, but still have not carried out the fish auction process itself but are auctioned by middlemen / pengambek . 2) the obstacles of the Paiton TPI in conducting the auction process. First, the price of fish auctioned by the Paiton TPI tends to be cheaper. Second, the attachment of capital to pengambek middlemen and lack of access to capital for fishermen. Third, there is still fish sales tax. 3) According to Imam Syatibi's Maqashid sharia review regarding safeguarding assets to improve the welfare of fishermen in Paiton District, it has been optimally categorized in the form of Dharurriyat such as property ownership and the prohibition of taking other people's property. Fulfillment of the hajiyyat aspect of understanding the shari'a of buying and selling and providing capital to fishermen, and tahsiniyyat such as avoiding deception and deception in the fish auction transaction process.